A cross-sectional study on prevalence of self-reported morbidity among elderly aged above 60 years residing in urban slums of Kurnool District, Andhra Pradesh, India - S. Cynthia Subhaprada; Mullangi Thanuja; U. Venkateswarlu (MRIMS Journal of Health Sciences, 2025)
Background: Aging is a natural, complex, and irreversible physiological process. It causes multiple organs and systems to deteriorate at the same time. The Indian elderly population is currently the world’s second largest. Morbidity is defined as the attributes of sickness such as illness, disability, handicap, and other compromised states of physical, social, and mental well-being. Objectives: The objective of the study was to study the sociodemographic profile of the study participants and to determine the prevalence of morbidity among elderly people living in urban slums. Materials and Methods: A community-based cross-sectional study was conducted in the selected urban slums from January 2021 to October 2022, among elderly persons aged 60 years and above. The total sample size obtained was 336 by multistage simple random sampling method. Morbidity was determined by self-reported symptoms of the study participants. Physical functioning limitation was assessed by the Medical Outcome Study-Physical Functioning Scale, and mental health was assessed by the Geriatric Depression Scale. Statistical analysis was performed using MS Excel 2016 and SPSS version 2021. Results: Prevalence of morbidity was 100%. Majority (84.5%) had ocular morbidity, followed by musculoskeletal system morbidity (83.6%). Majority (67.6%) had moderate physical limitation, and 42.8% had mild depression. Conclusion: All the study participants had some kind of morbidity. Screening programs should be conducted regularly for detecting chronic diseases at an early stage. Awareness programs about regular medical checkups should be conducted more frequently for elderly people.